HUBUNGAN EKSTENSI TUNGKAI DAN POWER OTOT TUNGKAI DENGAN KEMAMPUAN SMASH GEDENG DALAM PERMAINAN SEPAK TAKRAW PADA TIM PSTI LUBUK DALAM KECAMATAN LUBUK DALAM KABUPATEN SIAK - Odi Alfath; Zainur Zainur; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract : This study aims to find out whether there is a Relationship of unequal Power and Extension limb muscles with the ability to smash gedeng game in sepak takraw team PSTI Lubuk Dalam Sub Lubuk Dalam Siak Regency. This type of penelitin is the research of the correlation, where the population in this research is a team of PSTI Bottom In Sub Bottom In Siak Regency, numbering 8 people. As for the technique of the sample used is the total sampling (samples saturated), where all the population be used as samples. Requirements analysis test normality test with liliefors and correlation on a significant α (0.05). The first analysis between the Leg Extension (X1) with ability Smash Gedeng PSTI team In the bottom (Y), where the extent of significant rtab α (0.05) = 0.754 means rrhitung (0.577) <rtab (0.754), meaning that the hypothesis was not accepted and there is a strong link between extension with limbs results Smash Gedeng PSTI Bottom team In Subdistrict Bottom In Siak Regency. Calculation analysis of both X2 and Y, with the ability to Smash Gedeng where significant level rtab on α (0.05) = 0, 754 means rrhitung (0.301) < rtab (0,754), which means that the hypothesis was not accepted and there is a strong link between Power limb muscles with the results Smash Gedeng team PSTI Bottom In Sub Bottom In Siak Regency, third leg extension relationship analysis (X1) power of limb muscles (X2) with ability Smash Gedeng (Y) in getting, where the extent of significant rtab on α (0.05) = 0, 754 meansi rrhitung (0.633) < rtab (0.754). Then it can be inferred that the relationship between (X1) and (X2) with (Y) or limb extension and power relations of limb muscles with the results Smash Gedeng is not significant.Keywords: Leg Extension, Power and Smash Gedeng